Selection of Reference Genes for Quantitative Real-Time PCR in Bamboo (Phyllostachys edulis) - Fan, Chunjie; Ma, Jinmin; Guo, Qirong; Li, Xiaotie; Wang, Hui; Lu, Mengzhu (PloS one, 2013)
The Moso bamboo (Phyllostachys edulis) is one of the most important forestry resources and plays essential ecological roles in southern China. A draft nuclear genome sequence is expected to be publicly available in the near future; an explosion of gene expression data related to the unique traits of Moso bamboo will undoubtedly follow. Reverse transcription quantitative real-time PCR ((RT-)qPCR) is a widely used method for gene expression analysis. A necessary prerequisite of exact and reliable data is the accurate choice of reference genes. In this study, 14 candidate reference genes were chosen, and their expression levels were assessed by (RT-)qPCR in a set of six tissue samples (root, stem, mature stem, leaf, flower, and leaf sheath) and at two developmental stages (before and after flowering) in bamboo specimens obtained in three locations. The stability and suitability of the candidate reference genes were validated using the geNorm, NormFinder and BestKeeper programs. The results showed that TIP41 and NTB were suitable reference genes across all the tissues and at the different developmental stages examined in this study. While the expression of the NTB, TIP41 and UBQ were the mostly stable in different plant tissues samples, the expression of the TIP41, NTB and CAC were ranked the most stable in bamboo plants at various developmental stages. AP2-like gene was further assessed by using the reference genes TIP41 and NTB in comparison to ACT. Significant difference of the expression profile of AP2-like demonstrated the importance of choosing adequate reference genes in bamboo. TIP41 and NTB were found to be homogeneously expressed and were adequate for normalization purposes, showing equivalent transcript levels in different samples. They are therefore the recommended reference genes for measuring gene expression in P. edulis.